(untitled) (Research, Society and Development, 2020)
This study aimed to map the physical activity program carried out by the Family Health and Primary Health Care Expanded Support Center in accordance with the guidelines of the Ministry of Health. Cartography is a methodological path. The documentary sources served as an analytical device for hermeneutic apprehension, through content analysis. There was a program with a frequency of one to two days a week, with predominantly resisted and flexibility exercises, performed with light to moderate intensity and an average duration of 24.11 minutes. The existence of complementary therapies and the multiprofessional approach that enhance intervention in the area of physical education is highlighted, seeking to overcome the technical rationality of hegemonic bodily practices, emphasizing the intersubjective dimensions of corporeality. In addition, the satisfaction of the investigated actors, recognized through the processes of subjectification on the lived experience, capable of promoting the practice of healthy habits in an empowered and responsible manner, contributing to the adherence of these patients to the physical activity program.